AIAA Aviation 2019 Forum 2019
DOI: 10.2514/6.2019-3512
|View full text |Cite
|
Sign up to set email alerts
|

Defining Well Clear Separation for Unmanned Aircraft Systems Operating with Noncooperative Aircraft

Abstract: Detect-and-Avoid (DAA) systems are essential to the safe operations of Unmanned Aircraft Systems, and have the objectives of mitigating collisions with and remaining Well Clear of manned aircraft. This paper analyzes four candidate DAA Well Clear definitions for noncooperative aircraft using mitigated performance metrics of DAA systems. These DAA Well Clear definitions were proposed in previous work based on their unmitigated collision risk and maneuver initiation range. In this work they are evaluated using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Majority of encounters had a HMD and VMD greater than 2200 and 450 feet, respectively, at CPA. This combination of HMD and VMD are notable as it a separation metric used by RTCA SC-228 [27][28][29] and similar to separation criteria used by a different DAA standard published by ASTM F38 [30]. As the OpenSky Network-based model had 25% of encounters with a HMD and VMD of this or less, that encounter set was slightly more stressing to the DAA system and had encounters to estimate safety metrics based on that separation.…”
Section: Horizontal and Vertical Miss Distance Distributionsmentioning
confidence: 90%
“…Majority of encounters had a HMD and VMD greater than 2200 and 450 feet, respectively, at CPA. This combination of HMD and VMD are notable as it a separation metric used by RTCA SC-228 [27][28][29] and similar to separation criteria used by a different DAA standard published by ASTM F38 [30]. As the OpenSky Network-based model had 25% of encounters with a HMD and VMD of this or less, that encounter set was slightly more stressing to the DAA system and had encounters to estimate safety metrics based on that separation.…”
Section: Horizontal and Vertical Miss Distance Distributionsmentioning
confidence: 90%
“…In order to apply one of the candidate DWC definitions from Phase 2 to Phase 1 compliant UAS, it must be shown that the reduced DWC will not adversely affect the safety and alerting metrics. The effect of the reduced DWC on safety metrics is covered in another paper [17]. This paper uses simulation results that do not include any pilot actions to maintain DWC, referred to as "unmitigated" simulations, to determine the effects of a smaller DWC on alerting metrics for the Phase 1 UAS operations.…”
Section: Motivationmentioning
confidence: 99%
“…The proposed Phase 2 definitions reduced the horizontal miss distance and/or the modified Tau component but retained the 450 ft vertical miss distance. The proposed definitions were: Definition 1: 2,000 ft and 15 s; Definition 2: 2,200 ft and 0 s; Definition 3: 1,500 ft and 15 s; and Definition 4: 2,500 ft and 25 s (Chen et al 2019). The results of these simulations indicated that Definition 2 would preserve the most alerting time under reduced radar surveillance ranges associated with Low SWaP sensors.…”
Section: Introductionmentioning
confidence: 98%
“…The results of these simulations indicated that Definition 2 would preserve the most alerting time under reduced radar surveillance ranges associated with Low SWaP sensors. Monk, Rorie, Keeler, and Sadler (2020) reported the results of a human-in-the-loop simulation that modeled a UAS with a low SWaP radar (detection range = 3.5 nm) in order to compare DAA well clear Definitions 1 and 2 from Chen et al's (2019) study on pilot and DAA system performance. Twelve active-duty UAS pilots flew simulated UAS that were either slow (60 kts) or fast (100 kts) in speed.…”
Section: Introductionmentioning
confidence: 99%